English Speaking Skills and English Language Human Resource Development Affecting the Performance of Local Tourism Business - Thitivesa, Duangkamol (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Human resource development is the process in which organization improves their value, systems and performance by increasing the value of their employees. This human resource development includes the training, classes and growth opportunities that are given to employees for increasing their effectiveness as well as increase the success of companies. Objective of this study is to find out the impact of English-Speaking Skills and English Language Human Resource Development on the performance of local tourism business. Respondents of this study are employees working in the local tourism business of Thailand. Data is collected through the questionnaire via e-mail. Statistical tool applied on it. Results revealed that English speaking skills, English language and human resource development has positive significant impact on the performance of local tourism business. English language and English-speaking skills have positive significant impact on human resource development. Moreover, human resource development mediates the relationship between English speaking skills, English language and performance of local tourism business. Study suggest that for improving the business performance of local tourism give focus to human resource development.